Asymmetric wettable polycaprolactone-chitosan/chitosan oligosaccharide nanofibrous membrane as antibacterial dressings. (15th March 2023) - Kong, Yanhui; Zhang, Wenjing; He, Tian; Yang, Xue; Bi, Wanghua; Li, Jiwei; Yang, Wenzhe; Chen, Weichao
Abstract: Wound infection and inflammation hinder the process of wound healing and bother human beings chronically. As a naturally degradable macromolecule, chitosan (CS) has been widely used in antibacterial wound dressings. However, the antibacterial property of chitosan is inhibited by its water insolubility. In this study, we prepared a bilayered asymmetric nanofibrous membrane with the hydrophilic CS/chitosan oligosaccharide (COS) nanofibrous membrane as the bottom layer and the hydrophobic polycaprolactone (PCL) nanofibrous membrane as the top layer. Results showed that incorporating COS improved the CS membrane's wettability, and adding 0.5 % COS increased the inhibition zone diameter of Escherichia coli and Staphylococcus aureus by 23 % and 26 %, respectively. Moreover, the PCL layer could prevent the adhesion of water and bacteria. The PCL-CS/COS0.5% membrane showed relatively good mechanical properties, excellent water absorptivity (460 %), and appropriate cytocompatibility. This asymmetric wettable membrane has a massive potential to serve as a new antibacterial dressing for wound healing.